PENGARUH PENERAPAN PEMBELAJARAN AKIDAH AKHLAK BERBASIS PROBLEM BASED LEARNING TERHADAP MENINGKATKAN HASIL BELAJAR SISWA DI MTS AL-MUNAWARAH BINJAI UTARA - Maya Gustina; Tumiran Tumiran; Hadi Saputra Panggabean (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to analyze the effect of implementing a problem-based learning model on students’ learning outcomes in the Aqidah Akhlak subject at MTs Al-Munawwarah Binjai Utara. The background of this research is based on the low academic achievement and passive student participation caused by monotonous teaching methods. This study employs a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The sample consists of two classes: an experimental class applying the Problem-Based Learning (PBL) model and a control class using conventional methods. The research instrument was a multiple-choice test validated by experts. Data were analyzed using paired sample t-test and independent sample t-test with SPSS software. The Influence of the Aqidah Akhlak Learning Variable (X1) on the Student Learning Outcomes Variable (Y). The t-count value is 3.330 with α = 5%, t-table (5%; 31-3”- (1)”= 27) the t-table value is 1,70329. The Influence of the Problem Based Learning Variable (X2) on Learning Outcomes (Y). The t-count value is 3.787 with α = 5%, t-table (5%; 31-3”- (1)”= 27) the t-table value is 1,70329. The F-count value is 4.071 with α = 5%, while the f-table value for df=2,28 = 3,340. From the description, it can be seen that F count (4.071) > F table 3.340), and the significance value is 0.000 < 0.05, so it can be concluded that the hypothesis is accepted, meaning that Aqidah Akhlak Learning (X1) and Problem Based Learning (X2) have a significant influence together (simultaneously) on the student learning outcomes variable (Y). The R-square value is 0.571 or 57.1%. This indicates that the variables of Aqidah Akhlak Learning (X1) and Problem-Based Learning (X2) influence student learning outcomes (Y) by 57.1%. Therefore, the value is influenced by other variables unknown to the researcher.